2013
DOI: 10.1097/jom.0b013e3182a6bb75
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Workforce Health and Safety and the Health of the Bottom Line

Abstract: Companies that build a culture of health by focusing on the well-being and safety of their workforce yield greater value for their investors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 18 publications
0
60
0
Order By: Relevance
“…For example, the observed variability of work disability factors across age cohorts parallels the variability within a single diagnostic category. However, there is still not sufficient evidence to conclude that all key principles of workplace-centered work disability prevention apply equally across all conditions, as a few studies suggest otherwise [90]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, the observed variability of work disability factors across age cohorts parallels the variability within a single diagnostic category. However, there is still not sufficient evidence to conclude that all key principles of workplace-centered work disability prevention apply equally across all conditions, as a few studies suggest otherwise [90]. …”
Section: Resultsmentioning
confidence: 99%
“…70 We are aware of only 1 study that has examined the influence of a recognition program on company financial performance. In their study of the American College of Occupational and Environmental Medicine's Corporate Health Achievement Awards, Fabius and colleagues 71 showed that the highest-rated programs, per recognition program criteria, had superior financial performance compared with similar companies that had not been recognized by this program. There appear to be no studies that have associated performance against quality criteria of a recognition program with improvements in employee CVH risk factors over time.…”
Section: Current State Of Workplace Wellness Scorecards and Recognitimentioning
confidence: 99%
“…Transitioning employees to a CDHP can create challenges to well-being and may impact access to care by increasing the individual's share of health care costs. 7 A focus on a culture of well-being 22 , 23 can help to offset the potentially undesirable effects created by moving to a CDHP. This study demonstrates the possibility of achieving the dual goals of well-being improvement and health care cost reduction, and not just over 1 year but 5 years to both the employer and employee.…”
Section: Discussionmentioning
confidence: 99%